Nebulization metered-dose inhaler and spacer in bronchodilator responsiveness testing: a retrospective study - Rongli Lu; Ying Li; Chengping Hu; Pinhua Pan; Qiaohong Zhao; Ruoxi He (Therapeutic Advances in Respiratory Disease, 2023)
Background: The recommended delivery mode for bronchodilators in bronchodilator responsiveness (BDR) testing remains controversial. Objective: To compare the efficacy of salbutamol administration using a nebulizer versus a metered-dose inhaler (MDI) with spacer in BDR testing. Design: A retrospective study. Methods: This study examined the data of patients with chronic obstructive pulmonary disease who completed BDR testing between 1 December 2021 and 30 June 2022, at Xiangya Hospital, Central South University. After administering 400 μg of salbutamol through an MDI with spacer or 2.5 mg using a nebulizer, the changes in forced expiratory volume in one second (FEV 1 ) and forced vital capacity (FVC) were analyzed in patients with moderate-to-very severe spirometric abnormalities [pre-bronchodilator FEV 1 percentage predicted values (FEV 1 %pred) ⩽59%]. Significant responsiveness was assessed as >12% and >200 mL improvement in FEV 1 and/or FVC or >10% increase in FEV 1 %pred or FVC percentage predicted values (FVC%pred) from pre- to post-bronchodilator administration. Results: Of the enrolled 894 patients, 83.2% were male (median age, 63 years). After propensity score matching, 240 pairs of patients were selected. The increment in FEV 1 and increased FEV 1 relative to the predicted value (ΔFEV 1 %pred) were significantly higher in patients <65 years and those with severe spirometric abnormalities in the nebulization group than patients in the MDI group (all p  < 0.05). Compared with MDI with spacer, patients who used nebulization had a 30 mL greater increase in ΔFEV 1 (95% CI: 0.01–0.05, p  = 0.004) and a 1.09% greater increase in ΔFEV 1 %pred (95% CI: 0.303–1.896, p  = 0.007) from baseline. According to the > 12% and >200 mL increase criterion, the significant BDR rate with nebulization was 1.67 times higher than that with an MDI with spacer (OR = 1.67, 95% CI: 1.13–2.47, p  = 0.009). Conclusion: Salbutamol delivered using a nebulizer may be preferable to an MDI with spacer in certain circumstances. Nebulization has the potential to increase responsiveness to salbutamol in BDR testing.